TPCK (Technological Pedagogical and Content Knowledge) Competence for Educator: A Literature Review - Sihanita, Yudis Korin; Priambodo, Anung; Tuasikal, Abdul Rachman Syam (LP. Ma'arif Janggan Magetan, 2024)
This study aimed to analyze the competence of TPCK (Technological Pedagogical and Content Knowledge) in teachers through a literature review. The research conducted literature searches through academic databases, journals, books, and other sources of information using relevant keywords related to TPCK and the role of teachers in the context of technology use in teaching and learning. Subsequently, relevant literature was selected and evaluated for its quality, validity, and relevance to the research objectives. The analysis results indicated that teachers with high levels of TPCK tended to create more meaningful and profound learning experiences for their students. This suggested that TPCK development was a continuous process and required long-term commitment. Therefore, the role of TPACK in learning was crucial in supporting the sustainability of education.